Pathogenicity and virulence of Borrelia burgdorferi - Strnad, Martin; Rudenko, Natalie; Rego, Ryan O M (Virulence, 2023)
Infection with Borrelia burgdorferi often triggers pathophysiologic perturbations that are further augmented by the inflammatory responses of the host, resulting in the severe clinical conditions of Lyme disease. While our apprehension of the spatial and temporal integration of the virulence determinants during the enzootic cycle of B. burgdorferi is constantly being improved, there is still much to be discovered. Many of the novel virulence strategies discussed in this review are undetermined. Lyme disease spirochaetes must surmount numerous molecular and mechanical obstacles in order to establish a disseminated infection in a vertebrate host. These barriers include borrelial relocation from the midgut of the feeding tick to its body cavity and further to the salivary glands, deposition to the skin, haematogenous dissemination, extravasation from blood circulation system, evasion of the host immune responses, localization to protective niches, and establishment of local as well as distal infection in multiple tissues and organs. Here, the various well-defined but also possible novel strategies and virulence mechanisms used by B. burgdorferi to evade obstacles laid out by the tick vector and usually the mammalian host during colonization and infection are reviewed.
Keywords: Borrelia burgdorferi; virulence; pathogenicity; Lyme disease; Lyme Disease; Virulence Factors; tick-borne disease; zvířata; Humans; Virulence; faktory virulence; Mammals; virulence determinants; savci; clinical manifestations; lidé; lymeská nemoc; Animals